Formation of the measuring channel of multifunction phased array radar in tracking mode - О.Л. Cмірнов; О.А. Наконечний; А.В. Бологов (Наука і техніка Повітряних Сил Збройних Сил України)
In the article is considered the principle of the formation of the measuring channel for multifunction phased array radar in tracking mode using one of the short-range air defense radar system as an example. A new approach to the problem is offered, which is based on considering the change of noise levels both in the measuring channel and in the dynamic model of the target being tracked and is adaptive to its motion in space. The number of simultaneously monitored targets is calculated under the condition of application of the proposed principle of channel formation. The efficiency of the obtained solutions is confirmed. The conclusion is made about the expediency of application of this method in the existing air defense systems, the modernization of which is currently underway.